445 Vulvar verrucous carcinoma: 15 years experience in a single norwegian academic cancer center. (18th September 2019) - Nyberg, S; Davidson, B; Skeie-Jensen, T; Wang, Y
Abstract : Objectives: Vulvar verrucous carcinoma (VVC) is extremely rare, accounting for less than 1% of vulvar cancer cases. The purpose of this study was to report our experience with this disease. Methods: This is a retrospective study of patients with VVC who were treated at Oslo University Hospital between 2003 and 2018. Clinicopathological characteristics, treatment and follow-up were extracted from the medical records. Results: Seven patients were identified through pathology databases and verified as having VVC. The average age at diagnosis was 70 years. Four patients had previous Lichen sclerosus. Primary surgery was performed for all patients, including 3 wide local excisions, 1 simple local excision and 3 who underwent simple vulvectomies. Ipsilateral groin lymphadenectomy was performed for 1 patient because of uncertain histological result before surgery, showed negative lymph nodes. Tumor size and invasion depth ranged from 15 to 45 mm, 1 to 12 mm respectively. Tumor-free pathologic margin was achieved in 5 of 7 patients. Invasive disease extended to the pathological margin in 2 patients, re-excision was performed in 1 patient after primary simple local excision and the other patient was followed-up intensively without reoperation because of negative biopsy after primary wide local excision. The mean follow-up was 68 months with no recurrence in those 7 patients. Conclusions: VVC is defined by slow growth, no metastasis or lymph node involvement. The prognosis is relatively good, with low recurrent rate if wide local excision is performed. Overtreatment should be avoided. Patients with Lichen sclerosus in the vulva may have high risk for VVC.